Darkonia at colliders - Yang Bai; Susanne Westhoff (Journal of High Energy Physics)
Abstract Dark matter may form bound states in a dark sector with an attractive force between two dark matter particles. Searches for dark matter at colliders can differ dramatically from routine searches if bound states, dubbed darkonia, are produced and decay into visible Standard-Model particles. In this work, we use three representative models with scalar, pseudo-scalar, and vector force carriers to map out the darkonium signatures at both high-energy and low-energy colliders. Some of the bound states can be stable due to generalized parity and charge-conjugation symmetries, while others decay into light dark-force carriers, which subsequently can decay at a displaced vertex. New signatures with a mix of missing energy and multiple di-lepton or di-jet vertices reconstructing intermediate darkonium resonances are within reach at the LHC and Belle II.